IMPLEMENTATION OF MONITORING SIDE EFFECTS OF DRUGS IN DRUG-RESISTANT TUBERCULOSIS PATIENTS IN REFERRAL HOSPITALS: A QUALITATIVE STUDY - Elmiawati Latifah; Endang Yuniarti; Rinto Susilo; Hidayah Karuniawati; Azizah, Nur; Dyah Aryani Perwitasari; Syifa Imelda (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Drug-resistant tuberculosis (TB) is a public health problem that poses major challenges to patients, health workers, society, and the health care system. This research is a qualitative study to explore the implementation of drug side-effect monitoring and the role of health workers in handling side-effect monitoring medication for tuberculosis patients. We collected data through Focus Group Discussions (FGD) and conducted direct, in-depth interviews. The informants in this study were doctors, pharmacists, and nurses who were directly involved in treating drug-resistant tuberculosis patients. Two drug-resistant TB referral hospitals in the Cirebon area hosted the research. INVIVO 12 was used for qualitative analysis. Both hospitals still need to optimise the mechanism for tracking drug side effects in drug-resistant TB patients in accordance with the technical guidelines. Doctors at both hospitals play a significant role in implementation compared to other health workers. The similar role of doctors in both hospitals in implementation is in initial examination and history taking, determining causality, management, and education regarding drug side effects. Pharmacists have a similar role in managing drug side effects and documenting